PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA PAKAIAN BATIK TERHADAP MINAT BELI PELANGGAN PASAR TANAH ABANG - Dara, Nursimah; Purnaningsih, Nining (Universitas Muhammadiyah Tangerang, 2018)
The purpose of this research is to examine the effect of product quality and price on consumer buying interest in batik clothes Toko Muda Tanah Abang. The population in this research is all costumers of batik clothing of Toko Usaha Muda Tanah Abang, but the sample used with purposive sampling with customer criteria that have bought batik from Toko Usaha Muda Tanah Abang with the respondents as many as 20 customers. Technique of collecting data that is by method of questioner, interview and documentation. The variables studied include product quality and price as independent variable and buying interest as dependent variable. Data analysis using multiple linear regression. The result of analysis indicate that variable of product quality and pricing have positive and significant influence to the buying interest of Tanah Abang market. Keywords: Product Quality, Price, Interest Buy Consumer Clothing Batik